Impressive Nasal Septum Regeneration after Cord Blood Platelet Gel (CBPG) in Extreme Premature Neonate with Non-Invasive Ventilation: A Case Report - Raffaele Falsaperla; Giulia Marialidia Biondi; Milena Motta; Pasquale Gallerano; Giusi Tancredi; Piero Pavone; Martino Ruggieri (MDPI AG, 2022)
Background: We evaluated the efficacy of Cord Blood Platelet Gel (CBPG) in the regenerative reconstruction of the nasal septal tissue of a preterm infant undergoing non-invasive ventilation. Methods: A CBPC treatment was used to enhance the regeneration of the nasal septum of a premature patient in an experimental way, evaluating the efficacy described in the literature (selective bibliographic search in PubMed) of the use of blood products for non-transfusion purposes. Results: A partial but satisfactory regeneration of the patient's nasal septum was observed. Using the free NIH Image J online software, we were able to calculate the regenerated surface (about 83% of the destroyed cartilage). Conclusions: The use of platelet gel has been a promising alternative to surgical treatment in patients with severe damage to the nasal septum.